Vancomycin drug resistance, an emerging threat to animal and public health - Aqib, Amjad Islam; Alsayeqh, Abdullah F. (Frontiers in Veterinary Science, 2022)
With increasing demand of food keeping in view the rising human population, food production and processing is being revolutionized. Food production sources on the similar fashion are being obsessed with bacterial attack while use of antibiotics to counter them is posing another threat to the food safety and security. Advent of novel resistant genes like vancomycin resistance gene on one hand hampers effect of antibiotics while give rise to drug residues in food items. Currently a novel set of resistance gene “Van cluster” is circulating at all host and its environment level. Although it was considered as first line of choice against multiple drug resistant bacteria, but development of resistant strain has made it novel threat to the food animals and public health. Considerable economic losses in terms of low production and food safety requires immediate attention to control it. Current review revolves around development of vancomycin resistance and its impact on food safety.